2019
DOI: 10.1111/cmi.13031
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus parasuis infection in 3D4/21 cells induces autophagy through the AMPK pathway

Abstract: Haemophilus parasuis (H. parasuis) is a common commensal in the upper respiratory tract of pigs, but causes Glässer's disease in stress conditions. To date, many studies focused on the immune evasion and virulence of H. parasuis; very few have focused on the role autophagy played in H. parasuis infection, particularly in porcine alveolar macrophages (PAMs). In this study, a PAM cell line, 3D4/21 cells were used to study the role of autophagy in H. parasuis infection. 3D4/21 cells tandemly expressing GFP, mCher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…Similar findings were previously reported for L. infantum -infected BMM ( 9 ). This contrasts with several pathogens, including Mycobacterium tuberculosis , Haemophilus parasuis , Staphylococcus aureus , and Plasmodium falciparum , whose survival and replication were impaired by AICAR pretreatment of their host cells ( 88 90 ). Strikingly, the avirulent LPG-defective L. donovani Δ lpg1 mutant, which does not induce mitochondrial biogenesis, survived in BMM pretreated with AICAR.…”
Section: Discussionmentioning
confidence: 89%
“…Similar findings were previously reported for L. infantum -infected BMM ( 9 ). This contrasts with several pathogens, including Mycobacterium tuberculosis , Haemophilus parasuis , Staphylococcus aureus , and Plasmodium falciparum , whose survival and replication were impaired by AICAR pretreatment of their host cells ( 88 90 ). Strikingly, the avirulent LPG-defective L. donovani Δ lpg1 mutant, which does not induce mitochondrial biogenesis, survived in BMM pretreated with AICAR.…”
Section: Discussionmentioning
confidence: 89%
“…Some studies have examined the signalling pathway of autophagy induced by other porcine respiratory pathogenic bacteria. For example, in an in vitro study, Glaesserella parasuis ( Haemophilus parasuis ) was found to induce autophagy in 3D4/21 cells via the AMPK signalling pathway [ 37 ]. Some Mycoplasma species induce autophagy via the MAPK signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Sterile coverslips were placed into the bottom of 24-well plates and then inoculated with 3D4/21 cells (60% cell well confluency). Each cell well was inoculated with G. parasuis -5 at a dose of 400 MOI, and the cell plate was centrifuged at 800 × g for 10 min and then incubated at 37 °C for 1 h [ 13 ]. After washing 3 times with PBS, the infected cells on the coverslip were fixed with 4% formaldehyde.…”
Section: Methodsmentioning
confidence: 99%